0934 Ambulatory Blood Pressure Monitoring During Overnight Polysomnography in Children and Adolescents. (27th May 2020) - DelRosso, L M; Chan, J; Ruth, C; Arp, M; Ferri, R
Abstract: Introduction: During NREM sleep, sympathetic nervous system input decreases and systolic blood pressure drops. Sleep disorders can alter this mechanism. Ambulatory blood pressure monitors (ABPM) are increasingly used in children and are superior to clinic blood pressure in predicting cardiovascular morbidity and mortality. We aim to assess the effect of ABPM use during a sleep study in children and adolescents. Methods: Subjects were children ages 7-18 from Seattle Children's Hospital who underwent a sleep study for evaluation of suspected obstructive sleep apnea. Excluded children with known hypertension or taking a medication that altered blood pressure. An ABPM was placed on the right arm during the overnight sleep study and programmed to record BP every hour. Studies from children without OSA were analyzed for all sleep parameters. Data was compared with a control of children who underwent PSG and did not wear the ABPM. BP measurement was recorded and the PSG was reviewed for sleep stage, arousal, or awakening. Results: To date, we have 15 children with ABPM age mean 11.6, SD 2.9 and 35 controls age mean 10.97 and SD 3.1, age, sex and BMI did not vary between groups. None of the PSG parameters was statistically different between groups including total sleep time, sleep efficiency, arousal index or sleep stage distribution. An average of 10 BP readings was obtained per patient. 53% of BP readings in N1 resulted in awakenings, compared to 39% in N2, 5% in N3 and 14.8% in REM. Systolic, diastolic, heart rate and mean arterial pressure showed appropriate dipping during sleep with appropriate circadian increase at 4 AM. Pulse pressure remained the same. Conclusion: We have demonstrated the feasibility of using ABPM during PSG in children. Although sleep macroarchitecture did not show any significant difference in sleep efficiency or arousal index, further evaluation of each ABPM insufflation during the sleep study showed a sleep stage specific, sleep disruption with awakenings more likely to occur during N1 or N2 and less likely to occur during N3 or REM sleep. There was normal dipping and as expected circadian variability in the values. Support: